Comparative Genomics Provides Insights Into the Marine Adaptation in Sponge-Derived Kocuriaflava S43 - Sun, Wei; Liu, Changrong; Zhang, Fengli; Zhao, Mingzhu; Li, Zhiyong (Frontiers in Microbiology, 2018)
Sponge-derived actinomycetes represent a significant component of marine actinomycetes. Members of the genus Kocuria are distributed in various habitats such as soil, rhizosphere, clinical specimens, marine sediments and sponges, however, to date, little is known about the mechanism of their environmental adaptation. Kocuria flava S43 was isolated from a coastal sponge. Phylogenetic analysis revealed that it was closely related to the terrestrial airborne K. flava HO-9041. In this study, to gain insights into the marine adaptation in K. flava S43 we sequenced the draft genome for K. flava S43 by third generation sequencing (TGS) and compared it with those of K. flava HO-9041 and some other Kocuria relatives. Comparative genomics and phylogenetic analyses revealed that K. flava S43 might adapt to the marine environment mainly by increasing the number of the genes linked to potassium homeostasis, resistance to heavy metals and phosphate metabolism, and acquiring the genes associated with electron transport and the genes encoding ATP-binding cassette (ABC) transporter, aquaporin and thiol/disulfide interchange protein. Notably, gene acquisition was probably a primary mechanism of environmental adaptation in K. flava S43. Furthermore, this study also indicated that the Kocuria isolates from various marine and hyperosmotic environments possessed common genetic basis for environmental adaptation.